THE ERROR ANALYSIS OF ARABIC PRONUNCIATION OF STUDENTS CHOIR IN SINGING QASIDAH BUSYRA LANA - Muhammad Rifai; Toto Suharto (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
The article discusses the analysis of errors in the pronunciation of Arabic letters in members of the IAIN Surakarta’s PSM. This study describes: 1) the form of errors in the pronunciation of Arabic letters; and 2) factors causing the occurrence of pronunciation errors in Arabic letters. The method used is a descriptive qualitative method by analyzing the pronunciation errors in singing Qasidah songs. The research findings that 1) The form of pronunciation mistakes made on al-halaq (ع) mistakes made by respondents in the pronunciation of Arabic letters amounted to 6 errors. 2) Forms of pronunciation errors in al-lisan (ش، ض، ط، ص), pronunciation mistakes made amounted to 2-6 errors. Causes of errors or difficulties in pronouncing the letters al-halaq (throat) and al-lisan (tongue), among others: 1) The influence of mother tongue or first language. 2) Lack of reading practice. 3). There are still many members who aren’t graduated from Islamic boarding schools. These findings can be concluded the misreading of the Arabic letters in singing Qasidah, occurs due to the limitations of the IAIN Surakartas PSM members in pronouncing Arabic pronunciations and still being influenced by the mother tongue and limitations in adding material about pronunciation related to Arabic.